2020
DOI: 10.1590/1984-0462/2020/38/2018123
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and the Use of Probiotics in Constipation in Children and Adolescents: Systematic Review

Abstract: Objective: To perform a systematic review of literature data on gut microbiota and the efficacy of probiotics for the treatment of constipation in children and adolescents. Data source: The research was performed in the PubMed, the Scientific Electronic Library Online (SciELO) and the Latin American and Caribbean Health Sciences Literature (LILACS) databases in English, Portuguese and Spanish. All original articles that mentioned the evaluation of the gut microbiota or the use of probiotics in children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…To date, five studies have investigated the gut microbiome of children with constipation ( 51 , 52 ). Zhu and collaborators ( 28 ) carried out the first study using 16s rRNA gene pyrosequencing, finding that obese children with constipation consumed less fiber and had lower levels of Prevotella and increased levels of butyrate-producing taxa ( Coprococcus, Roseburia , and Faecalibacterium ) than controls.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, five studies have investigated the gut microbiome of children with constipation ( 51 , 52 ). Zhu and collaborators ( 28 ) carried out the first study using 16s rRNA gene pyrosequencing, finding that obese children with constipation consumed less fiber and had lower levels of Prevotella and increased levels of butyrate-producing taxa ( Coprococcus, Roseburia , and Faecalibacterium ) than controls.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Paradoxically, more research has been conducted on the effects of probiotics than on the gut microbiome itself. The latest systematic review ( 51 ) assessed eight randomized placebo-controlled trials (RCTs) which investigated the role of various strains of probiotics on the treatment of childhood FC. Only one RCT showed significant improvement in stool frequency and consistency, and reduction in abdominal pain using Lactobacillus casei rhamnosus Lcr35 ( 64 ), however, these findings were contradicted by a later trial ( 65 ), and the pooled results of the two RCTs showed no statistical significance for treatment success ( 66 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although the human microbiome comprises more than 400 bacterial species, evidence has shown that a decrease in the population of Bifidobacterium and Lactobacillus in adults can result in intestinal constipation. [ 12 14 ] Consequently, the probiotics used in humans for the treatment of constipation are more often of the species Lactobacillus and Bifidobacterium . According to Ceresola et al [ 8 ] these Lactobacillus and Bifidobacterium can shorten the migratory myoelectric complex period and accelerate small intestine transit, partly due to increased release of serotonin (5-HT) which has promotility effects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] However, there is no consensus on probiotic strains and dosages for the treatment of constipation. [ 12 , 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on a systematic review of literature data on gut microbiota, Gomes et al . also considered that there is still no basis for recommending probiotics for the treatment of constipation in children and adolescents …”
mentioning
confidence: 99%